A STUDY ABOUT TECHNOLOGIES FOR EAD EDUCATION - Alves, Mailson Moreira; Romeiro, Rafael Rodrigues; Araújo, Liriane Soares (Revista Interface Tecnológica, 2022)
Considering the growth in demand for distance education courses and some social situations, it is relevant to address the technologies that are related to this context, covering the impact they bring to educational institutions and consequently to teachers and students who use them, emphasizing their advantages and disadvantages in order to better use such technologies and contribute to the literature. The research methodology of this work involves conducting a survey in an institution to obtain a qualitative data collection through a questionnaire, in which students were required to answer questions about the institution and the technologies being used. Based on this data collection, the answers were analyzed, bringing suggestions on how educational institutions can use such technologies to obtain a better use of learning by the user on the distance learning platform.
Keywords: Ead; Distance Education; Teaching; Education; Learning; Technology; Platform